Determination of European vector of insurance development of vehicle owners’ civil liability - Березіна, Світлана Борисівна (Technology audit and production reserves, 2017)
An analysis of Ukrainian insurance market for vehicle owners’ civil liability is carried out in the article. The main purposes of insurance coverage for compulsory insurance of vehicle owners’ liability are defined. The key issues of bringing a compulsory insurance of vehicle owners’ civil liability into line with European standards are defined. Stages of implementation of key aspects of bringing a compulsory insurance of vehicle owners’ civil liability into line with European guidelines are studied. An implementation of compulsory insurance of vehicle owners’ civil liability is associated with the need to compensate the damage of life, health and/or property of injured in the accident and the protection of property interests. The level of compulsory insurance of vehicle owners’ liability in the insurance market of Ukraine lags behind the level of foreign markets. In terms of European integration, there is an urgent need to find ways of bringing a compulsory insurance of vehicle owners’ civil liability into line with European standards. The results of the analysis of domestic market of compulsory insurance of vehicle owners’ civil liability could argue that implementation of reform measures is realized for all purposes to bring the market into line with European standards. This research may be useful as a part of the program of Ukrainian insurance market development, which will contribute to national economic development and will have confidence and be competitive in the global insurance market.